2021
DOI: 10.3892/etm.2021.10967
|View full text |Cite
|
Sign up to set email alerts
|

Role of AUF1 in modulating the proliferation, migration and senescence of skin cells

Abstract: AU-rich element RNA-binding factor 1 (AUF1) is a classical RNA-binding protein. AUF1 influences the process of development, apoptosis and tumorigenesis by interacting with adenylate-uridylate rich element-bearing mRNAs. Human skin is the largest organ of the body and acts as a protective barrier against pathogens and injuries. The aim of the present study was to explore the function and potential molecular pathways of AUF1 in human skin cells. AUF1 was overexpressed in human keratinocyte HaCaT cells and human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…In addition to these tantalizing bits of data suggesting a prominent role for AUF1 in cardiomyocyte pathophysiology, there are also reports of AUF1 regulation of proliferation, migration, and cell senescence in skin and breast cancer associated fibroblasts that have gone unrealized in the cardiac field ( Hendrayani et al, 2014 ; Wallis et al, 2015 ; Hendrayani et al, 2016 ; Yu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these tantalizing bits of data suggesting a prominent role for AUF1 in cardiomyocyte pathophysiology, there are also reports of AUF1 regulation of proliferation, migration, and cell senescence in skin and breast cancer associated fibroblasts that have gone unrealized in the cardiac field ( Hendrayani et al, 2014 ; Wallis et al, 2015 ; Hendrayani et al, 2016 ; Yu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, these data hinted at the signi cance of AUF1 in the process of oncogenesis (20). A study on human skin cells recently suggested that the overexpression of AUF1 promoted migration and proliferation of human skin cells, accelerated the healing of wounded skin, and AUF1 overexpression inhibited cell apoptosis, the knockdown of which promoted cell senescence (21).…”
Section: Introductionmentioning
confidence: 99%